Culture and Gender Allocation of Tasks: Source Country Characteristics and the Division of Non-Market Work among US Immigrants - Francine D. Blau; Lawrence Kahn; Matthew Comey; Amanda Eng; Pamela Meyerhofer; Alexander Willén (Center for Economic Studies and ifo Institute (CESifo), 2020)
There is a well-known gender difference in time allocation within the household, which has important implications for gender differences in labor market outcomes. We ask how malleable this gender difference in time allocation is to culture. In particular, we ask if US immigrants allocate tasks differently depending upon the characteristics of the source countries from which they emigrated. Using data from the 2003-2017 waves of the American Time Use Survey (ATUS), we find that first-generation immigrants, both women and men, from source countries with more gender equality (as measured by the World Economic Forum's Global Gender Gap Index) allocate tasks more equally, while those from less gender equal source countries allocate tasks more traditionally. These results are robust to controls for immigration cohort, years since migration, and other own and spouse characteristics. There is also some indication of an effect of parent source country gender equality for second-generation immigrants, particularly for second-generation men with children. Our findings suggest that broader cultural factors do influence the gender division of labor in the household.
Keywords: J13; J15; J16; J22; 330; housework; childcare; gender; immigration; time allocation